2016
DOI: 10.1039/c6ta00513f
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric oxide surface chemistry: water splitting via pyroelectricity

Abstract: We propose a cyclic catalytic system that splits water by harnessing the pyroelectric effect in ferroelectric oxides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
94
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(97 citation statements)
references
References 191 publications
3
94
0
Order By: Relevance
“…At higher temperatures, dissociative adsorption of 18 O2 and CO helps to fill the vacant sites (ii) and leave adsorbed O* and C* (iii), permitting CO2 formation via adsorbate reaction (iv) or through direct combination of incoming O2 with C* or incoming CO with O* (v) (the Eley-Rideal mechanism) [143]. Although BaTiO3 did not demonstrate high activity in this study, recent calculations have predicted better results for other ferroelectric materials and reactions when following particular polarization/catalytic cycles [144,145]…”
mentioning
confidence: 72%
“…At higher temperatures, dissociative adsorption of 18 O2 and CO helps to fill the vacant sites (ii) and leave adsorbed O* and C* (iii), permitting CO2 formation via adsorbate reaction (iv) or through direct combination of incoming O2 with C* or incoming CO with O* (v) (the Eley-Rideal mechanism) [143]. Although BaTiO3 did not demonstrate high activity in this study, recent calculations have predicted better results for other ferroelectric materials and reactions when following particular polarization/catalytic cycles [144,145]…”
mentioning
confidence: 72%
“…[27] Thirdly,m ore effective external polarization methods need to be developed. Similar to stress-induced piezoelectric polarization, temperature fluctuation of pyroelectrics gives rise to polarization of an electric field, [56] and may promote the separation of photoexcited e À and h + . should be exploited as an excitation source and could also advance the practical applications of photocatalysis.…”
Section: Discussionmentioning
confidence: 99%
“…are highly anticipated. Similar to stress-induced piezoelectric polarization, temperature fluctuation of pyroelectrics gives rise to polarization of an electric field, [56] and may promote the separation of photoexcited e À and h + .…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced carrier separation as ar esult of the polarization is expected to enable ad rastically improved catalytic performance.I na ddition, for the normal catalytic process,a nother problem that limits the catalytic activity is the correlation among the binding energies of catalysts, reactants,i ntermediates,a nd products (described as the scaling relationship), which follows the Sabatier principle.I t is notable that the interaction between catalysts and adsorbates is neither too weak to hinder the adsorption of reactants onto the surface of catalysts nor too strong to prohibit the desorption of products from the surface of catalysts.Periodic stress applied on the catalysts favors the adsorption and desorption processes of reactants and products,r espectively, mediated by the periodic polarization. [8] Finally,other forms of clean energy,including wind, tidal, and geothermal energy,c an also be exploited as energy sources to trigger the PIEZOcatalysis.W ind and tide can be utilized to apply stress on catalysts,w hile geothermal energy can be employed as the heat source to change the temperature of catalysts.A ss uch, ag reater progress in the wide spectrum of practical utilization of PIEZOcatalysts will be facilitated.…”
Section: Discussionmentioning
confidence: 99%
“…[7] DFT calculations showed that the built-in electric field also mediates the adsorption and desorption of reactants and products on the surface of piezoelectric catalysts,which is conducive to overcoming some fundamental limitations on catalysis caused by the Sabatier principle. [8] Moreover,p iezoelectric polarization was also reported to tune the catalytic rate by effectively adjusting the barrier height of aheterogeneous semiconductor interface. [9] This Minireview highlights recent development in PIE-ZOpotential-enabled catalysis that capitalizes on piezoelectric, pyroelectric,a nd ferroelectric semiconductors.W es ummarize the recent development of PIEZOelectric semiconductors,t heir PIEZOpotential-mediated catalytic mechanism, special techniques to tailor their piezoelectric proper-…”
Section: Introductionmentioning
confidence: 99%